PROMISING GENETIC STOCKS IDENTIFIED FROM MULTILOCATION VARIETAL EVALUATION TRIALS OF INSTITUTE-INDUSTRY COLLABORATIVE PROGRAMME IN TAMIL NADU - Hemaprabha, G; Appunu, Chinnaswamy; Mohanraj, K; Ram, Bakshi (Journal of Sugarcane Research, 2020)
Twenty elite sugarcane Co canes were tested in mutlilocation trials at 10 locations of Tamil Nadu under Institute-Industry collaborative programme. These genotypes were evaluated under randomized block design with three replications; yield and quality contributing parameters were recorded at 240, 300 and 360 days after planting. Analysis revealed the superiority of Co 13001 for early sucrose accumulation potential at 240 days and Co 14016 for good ratoonability potential with high cane yield through increased millable cane population.